Tata Kelola Perusahaan dan Keberlanjutan: Kinerja Triple Bottom Line - Eka Murtiasri; Prianka Ratri Nastiti; Moh Haris (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2023)
The purpose of this study is to examine the effect of corporate governance on the performance of triple bottom line sustainability. Corporate governance is embodied in the number of Directors, the percentage of female Directors, expertise and frequency of meetings. The sustainability performance is proxied by the dimensions of sustainability: economic, environmental and social. The sample of this research are companies listed on the IDX 2020-2021 indexed LQ 45. Sampling was based on purposive random sampling which resulted in 52 data. Hypothesis testing was done by multivariate regression. Agency theory and Stakeholder theory are used as the theoretical basis for discussion. The test results that the greater the number of Directors has a negative effect on the economic, environmental and social performance. The large percentage of the number of female Directors has a positive effect on social performance, while the effect of the frequency of Directors' meetings has a positive effect on economic and environmental performance. The expertise of the Board of Directors has absolutely no effect on all dimensions of sustainability performance.